L’influence des présuppositions sur les témoignages sollicités par questions - Elizabeth Allyn Smith; Myriam Raymond-Tremblay (Discours)
Loftus (1975) and subsequent established that presupposing new information during witness questioning can influence subsequent eyewitness reports. We report on a study that attempts to replicate these results for another language (French) in order to better understand some of the factors that facilitate (or not) disinformation. Our sixty participants watched a video of an attempted robbery and answered questions in which the existence of an element was (a) a true presupposition, (b) a false presupposition, or (c) not presupposed. A week later, all participants received a second questionnaire where the critical information was questioned, followed by a working memory task and a demographic survey. Our analysis (by binomial logistic regression) tests the proportion of false responses to the second survey by condition. Our results show that presuppositions of true information significantly decrease the rate of false responses (p